Pengaruh Program Pendidikan dan Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Pegawai pada PT. TASPEN (PERSERO) Cabang Surakarta - Syaifuddin, Azhar; , Drs. Agus Moqorobin, M.M (2016)
The objectives of this research were to analyze and to know how big the influences of workshop program and the influences of work environment on the employees' performance of PT. TASPEN (Persero) of Surakarta Branch were and to obtain description and explanation on the implementation of workshop program at the company. Based on the results of the research, it was hoped that the results could give contributions and information for the company which would be made as consideration materials in the effort of increasing or developing workshop and work environment on the employees' performance in future. Sample used in this research was as many as 34 respondents. The technique used in this research was Validity Test using the method of corrected item-total correlation, Reliability Test using cronbach's alpha, Analysis of Multiple Linear Regression, Normality Test using kolmogorov-smirnov, t Test, F Test, and Coefficient of Determination. The sample was taken through purposive sampling which is a technique of sampling based on the purpose. The results of this research were that in the t Test, all variables in this research separately had a significant influence on the employees' performance of PT. TASPEN (Persero) of Surakarta Branch. In the F Test, simultaneously and collectively, variable of workshop and variable of Work Environment had significant influences on the Employees' Performance. Meanwhile, in the Coefficient of Determination (R2), the contribution of the variable of Workshop and the variable Work Environment could explain the variable of Employees' Performance as much as 68.8% and the rest was influenced by other factors as much as 31.2% (100% - 68.8%).